THE EFFECT OF GIVING DRAGON FRUIT PEEL JUICE ON THE DRINKING WATER ON 6 WEEKS OLD QUAIL CARCASS PARTS - O., Graciella; Dewi, G. A. M. K.; Wirapartha, M. (Jurnal Peternakan Tropika, 2022)
This study aims to determine the carcass parts of quail aged 6 weeks given dragon fruit peel juice. This research was conducted in December 2020 at Mr. Anwar House, Pasraman Unud Housing, Blok F-30 and Poultry Laboratory, Faculty of Animal Husbandry, Udayana University. This study used a completely randomized design (CRD) with four treatments and four replications. The four treatments were: water without dragon fruit peel juice or control (P0), drinking water given dragon fruit peel juice as much as 1% (P1), drinking water given dragon fruit peel juice as much as 2% (P2), drinking water given dragon fruit peel juice as much as 3% (P3). The variables observed were cut weight, carcass weight, carcass percentage and carcass chips (chest, back, wings, thighs). The results of giving dragon fruit peel juice in this study showed that the cut weight, carcass weight, carcass percentage and carcass weight (chest, back, wings, thighs) were not significantly different (P> 0.05) in all treatments. The conclusion of this study showed that giving dragon fruit peel juice with a concentration of 0%,1%, 2% and 3% in drinking water has no effect on cut weight, carcass weight, carcass percentage, and percentage of carcass parts (chest, back, wings, thigh) 6 week old quail.   Keywords: Coturnix-coturnix japonica quail, percentage of carcass parts, dragon fruit skin (Hylocereus polyrhizus)